YouTube teaching materials with peer support to improve students' mastery of subject content learning - Asnawi Muslem; Rosnani Sahardin; Hendra Heriansyah; Ika Apriani Fata; Yulianti Djalaluddin; Emma Hankinson (Universitas Syiah Kuala, 2022)
This study investigated the effectiveness of using YouTube teaching materials with peer support on students’ mastery of subject content learning, motivation, obstacles, and benefits they acquired in learning through this media. This study involved 60 undergraduate students attending the English Language Teaching Method Course (ELTMC) at a university in Banda Aceh, Indonesia. The study used mixed methods: quantitative and qualitative. A quasi-experimental with pre-test and post-test design was used to see the effectiveness of using YouTube teaching materials with peer support and without peer support on students’ mastery of the course. The instruments used to collect the data were tests and an open-ended questionnaire. The findings revealed that using YouTube teaching materials with peer support significantly improved students’ mastery of the subject content of ELTMC compared to those without peer support. The study also reported that only 13 of 30 students had problems learning the subject via the media in the experimental group with peer support. The problems were the speed of speaking by the native speakers, lengthy videos, different English accents that were difficult to absorb, and unclear video sounds. Meanwhile, the benefits include the presence of the native speakers in the videos who are creative and accurate in the language being learned (i.e., English), the joy and positive challenges they got from watching the videos and having discussions afterward with peers. The availability of peer assistance enabled students to comprehend the teaching material delivered through actual media on YouTube on a deeper level.